PENERAPAN METODE CERTAINTY FACTOR UNTUK MENDETEKSI PENYAKIT HYDROCHEPALUS BERBASIS WEB - Muliati Badaruddin (Teknosains, 2016)
Hydrocephalus is disease that occurs resulting from disruptionthe flow of a liquid in the brain (a liquid serebro spinal) or accumulatedcerebrospinal fluid in the ventricles of cerebral , the subarachnoid space , orspace subdural. The disruption is causes the liquid the increase in manywhich then pressing brain tissue around it, especially nerve centers was vital. This research aims to devise an expert system that implements the methodof Certainty Factor ( CF ) is the value of certainty factors as the value ofclinical parameters given MYCIN to indicate the level of confidence is basedon the hypothesis that are affected by symptoms (evidence ) of a disease.Expert systems are designed based on the knowledge of specialists andassociated research on diseases Hydrocephalus is further applied on theexpert system by applying the method certainty factor whose output can beseen through the medium of a computer connected to the Internet network , itis intended to be known by the public to anticipate and know the earlysymptoms of the disease Hydrocephalus and the prevention and earlytreatment of the disease before it 's too late to be addressed.